Reflective Study of Qashidah Burdah as a Medium for Strengthening Religious Moderation at Majelis Nurul Musthafa Palur, Sukoharjo: Kajian Reflektif Qashidah Burdah sebagai Media Penguatan Moderasi Beragama di Majelis Nurul Musthafa Palur, Sukoharjo - Alif Al Hilal Ahmad; Suryo Ediyono; Muhammad Farkhan Mujahidin; Abdul Malik; Ahmad Jazuli (Room of Civil Society Development, 2026)
This community service activity aimed to strengthen the values of religious moderation among the congregation of Majelis Nurul Musthafa, Turisari, Palur, Mojolaban, Sukoharjo, through an in-depth study of the meaning of Qashidah Burdah by Imam al-Busiri. The activity was motivated by the need to transform the recitation of Qashidah Burdah from a routine religious practice into a reflective learning process that emphasizes moral, spiritual, and social values. This program used a descriptive-qualitative approach with participatory and reflective methods, involving the congregation as active participants in the learning process. The stages of the activity included initial observation, socialization of religious moderation, thematic study of selected verses of Qashidah Burdah, reflective discussion, and assistance in preparing the annual da’wah theme of the majelis. The results showed that the congregation began to understand Qashidah Burdah not only as a text of praise to Prophet Muhammad, but also as a source of values related to gentleness, tolerance, balance, moral exemplarity, and universal compassion. The activity also resulted in the formulation of an annual study theme based on religious moderation and the formation of moderate da’wah cadres. This community service contributes to developing a model of cultural da’wah based on classical Islamic literature, religious literacy, and community-based character education.